Role of Risk Factors in the Incidence of Multidrug-Resistant Tuberculosis - Khairani, Alya Putri; Santoso, Prayudi; Setiawati, Elsa Pudji (International Journal of Integrated Health Sciences, 2017)
Objective: To determine the risk factors that played roles in the incidence of multidrug-resistant tuberculosis (MDR-TB) in such patients. Multidrug-Resistant Tuberculosis is a form of tuberculosis caused by Mycobacterium tuberculosis that is resistant to at least isoniazid and rifampicin.Methods: This was a case control study to compare MDR-TB to non-MDR-TB pulmonary tuberculosis outpatients in Dr. Hasan Sadikin General Hospital, Bandung on August–September 2014. Fifty MDR-TB outpatients were included as the cases and 50 non-MDR-TB outpatients as controls. Data was collected by questionnaires and patient’s registration forms. Bivariate and multivariate analyses were performed using chi-square test and multiple logistic regression test, with p<0.05 considered significant. Results: From bivariate analysis, number of previous tuberculosis treatments, regularity of previous treatment, and burden of cost were significant risk factors for developing MDR-TB (p<0.05); while from multivariate analysis, number of previous TB treatments was the only risk factor that played a significant role in the incidence of MDR-TB (OR 24.128 95% CI 6.771-85,976). Conclusions: Patients and medication factors are risk factors that play roles in the incidence of MDR-TB. The significant risk factor is the number of previous TB treatment. Keywords: Multidrug-resistant tuberculosis, resistance, risk factors, tuberculosis DOI: 10.15850/ijihs.v5n2.991